(untitled) (INTERNATIONAL CONFERENCE ON ADVANCE SCIENCE AND TECHNOLOGY, 2025)
In this article, you can learn about the socio-pedagogical significance of using digital technologies in teaching English to non-philological students in education, as well as the problems and shortcomings that arise in this regard and methodological solutions.